Null Subjects in Swabian. (8th September 2013) - Bohnacker, Ute
Abstract Few studies have investigated referential null subjects in present‐day non‐standard varieties of German. This paper explores the distribution of 4, 000 null and overt referential subjects in finite clauses in a new corpus of spoken Swabian, a North Alemannic dialect spoken in Southwest Germany. The paper describes Swabian subject use as it emerges from the corpus data with regard to morphological form, syntactic distribution, reference and informational status. Swabian, unlike Standard German, allows and in some cases prefers clause‐internal referential subjects to be null, whilst in other contexts, referential null subjects are ruled out. There is a robust second person null‐subject property, with 61% of 2nd singular subject pronouns being dropped clause‐internally, i.e. from a position following the finite verb in main clauses or following a complementiser in embedded clauses. 1st singular and 3rd singular neuter subjects are dropped clause‐internally as well, but at much lower frequencies and only in very specific phonological and lexical constellations, not previously noted in the literature. The empirical findings are compared with an earlier unquantified study of Swabian (Haag‐Merz 1996) and discussed in light of other work on present‐day Germanic vernaculars and previous accounts of partial null subject languages.